States and their nationals abroad support, co-opt, repress - Brummer, Klaus 1977-; Ganguly, Sumit 1954- (Cambridge University Press, 2025)
In a novel contribution to the field of comparative foreign policy analysis, this book carefully delineates how states, regardless of regime, have formulated policies to deal with their national communities aboard. Some states, depending on their domestic political ideologies, cultures and capabilities, have extensive institutional mechanisms in place for coming to the aid of their nationals abroad. Others, however, have also used these capabilities in adverse ways. Chapters focusing on individual countries explore the rationale behind state policies that differentiate treatment for distinct groups, such as tourists, migrants, and diasporas. Amongst the intriguing findings is the fact that state capacity alone does not explain the ability or willingness of states to assist their nationals abroad in times of need. Furthermore, in some cases, communities abroad can also actively mobilize against their home state, thus play key roles in conflict and even regime change